Effects of armed conflict on maternal and infant health: a mixed-methods study of Armenia and the 2020 Nagorno-Karabakh war - Araz Chiloyan; Lara Rostomian; Elizabeth Hentschel; Carmen Messerlian (BMJ Open)
Introduction Armed conflict worldwide and across history has harmed the health of populations directly and indirectly, including generations beyond those immediately exposed to violence. The 2020 war between Armenia and Azerbaijan over Nagorno-Karabakh, inhabited by an ethnically Armenian population, provides an example of how conflict harmed health during COVID-19. We hypothesised that crises exposure would correspond to decreased healthcare utilisation rates and worse health outcomes for the maternal and infant population in Armenia, compounded during the pandemic.Methods Following a mixed-methods approach, we used ecological data from 1980 to 2020 to evaluate health trends in conflict, measured as battle-related deaths (BRDs), COVID-19 cases, and maternal and infant health indicators during periods of conflict and peace in Armenia. We also interviewed 10 key informants about unmet needs, maternal health-seeking behaviours and priorities during the war, collecting recommendations to mitigate the effects of future crisis on maternal and infant health. We followed a deductive coding approach to analyse transcripts and harvest themes.Results BRDs totalled more in the 2020 war compared with the previous Nagorno-Karabakh conflicts. Periods of active conflict between 1988–2020 were associated with increased rates of sick newborn mortality, neonatal mortality and pre-eclampsia or eclampsia. Weekly average COVID-19 cases increased sevenfold during the 2020 Nagorno-Karabakh war. Key informants expressed concerns about the effects of stress and grief on maternal health and pregnancy outcomes and recommended investing in healthcare system reform. Participants also stressed the synergistic effects of the war and COVID-19, noting healthcare capacity concerns and the importance of a strong primary care system.Conclusions Maternal and infant health measures showed adverse trends during the 2020 Nagorno-Karabakh war, potentially amplified by the concurrent COVID-19 pandemic. To mitigate effects of future crises on population health in Armenia, informants recommended investments in healthcare system reform focused on primary care and health promotion.